Clinical features and immune-related protein patterns of anti-MDA5 positive clinically amyopathic dermatomyositis Dutch patients. (20th January 2022) - Hensgens, Marjolein P M; Delemarre, Eveline M; Drylewicz, Julia; Voortman, Mareye; Krol, Roline M; Dalm, Virgil A S H; Miedema, Jelle R; Wiertz, Ivo; Grutters, Jan; Limper, Maarten; Nierkens, Stefan; Leavis, Helen L
Abstract: Objectives: The presence of melanoma differentiation-associated protein 5 (MDA5) antibodies in patients with DM is associated with the development of a rapidly progressive interstitial lung disease (RPILD), unresponsive to conventional treatment. We characterize patients and provide more insight into potential biomarkers to identify patients with RPILD. Methods: Patients diagnosed with anti-MDA5 positive DM between December 2015 and November 2017 were included in this study. Clinical data were retrospectively retrieved from medical records. A total of 180 immune-related markers were measured in sera of 16 patients and 15 healthy controls using proximity extension assay-based technology. Results: Twenty patients were included, with a median time from symptoms till diagnosis of 4 months. All patients had clinically amyopathic DM. Interstitial lung disease (ILD) was present at diagnosis in 94% of the patients, 45% presented with RPILD. The mortality rate was 35% within 4 months after diagnosis and respiratory failure was the main cause of death in these patients. Furthermore, unsupervised analysis revealed that patients with RPILD show clearly different inflammatory serum profiles than healthy controls. In addition, in comparison to healthy controls, the IFN, IL1, IL10 and IL18 signalling pathways are different regulated in anti-MDA5 positive patients. Conclusion: In this Dutch anti-MDA5 positive clinically amyopathic DM (CADM) cohort, one-third of the patients died due to RPILD soon after diagnosis, which underlines the severity of this disease. In addition, we have found several possible pathways that are differentially regulated in RPILD vs no RPILD DM and healthy controls. These markers await further validation before clinical use.